India : Why Fiscal Adjustment Now - Pinto, Brian (World Bank: Washington, DC, 2013)
India's growth performance has been impressive over the last two decades. But its sustainability has been in question, first with the 1991 fiscal-balance of payments crisis (BoP), and then again after 1997/98, when fiscal deficits returned to the 10 percent of GDP range and government debt grew. This paper analyzes the deterioration in India's public finances and presents evidence suggesting that, in the absence of a fiscal adjustment, low inflation and high reserves may have been pursued at the expense of long-run growth and poverty reduction. Resolving this inflation-external vulnerability-growth policy trilemma requires fiscal adjustment. In making its case, the paper shows, first, that fiscal fundamentals have weakened after 1997/98 even when compared with the pre-1991 crisis period. This has continued in spite of the recent record lows in interest rates. Second, the fiscal stance is not conducive to long-run growth and poverty reduction because capital spending has been cut to accommodate higher interest payments and other current spending, with expenditures on the social sectors stagnating. Third, without a fiscal adjustment, the debt burden is likely to reach unmanageable levels by the end of the Tenth Plan period. In contrast, a phased adjustment beginning now and focusing on a relatively small set of reforms is likely to improve debt dynamics substantially over the same horizon, while also promoting faster growth and poverty reduction.